2016
DOI: 10.1007/978-94-017-7555-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Immunotherapy for Treatment of Cancer

Abstract: Immunotherapy entails the treatment of disease by modulation of the immune system. As detailed in the previous chapters, the different modes of achieving immune modulation are many, including the use of small/large molecules, cellular therapy, and radiation. Oncolytic viruses that can specifically attack, replicate within, and destroy tumors represent one of the most promising classes of agents for cancer immunotherapy (recently termed as oncolytic immunotherapy). The notion of oncolytic immunotherapy is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 280 publications
0
12
0
2
Order By: Relevance
“…Многочисленные исследования показали, что основным фактором эффективности онколитической виротерапии является способность вирусов стимулировать иммунные реакции. Молекулярные паттерны, ассоциированные с повреждением (DAMPdanger associated molecular patterns) и опухоле-ассоциированные антигены, высвобождаемые из лизированных опухолевых клеток, стимули-руют активацию как врожденных неспецифиче-ских иммунных реакций, так и формирование антиген-специфического противоопухолевого ответа [11,83]. Важную роль активации иммун-ного ответа подтверждают, в частности, экспе-рименты, проведенные в мышиной модели.…”
Section: Nepomnyashchikh Ts Et Al непомнящих тс и др Medical Imunclassified
“…Многочисленные исследования показали, что основным фактором эффективности онколитической виротерапии является способность вирусов стимулировать иммунные реакции. Молекулярные паттерны, ассоциированные с повреждением (DAMPdanger associated molecular patterns) и опухоле-ассоциированные антигены, высвобождаемые из лизированных опухолевых клеток, стимули-руют активацию как врожденных неспецифиче-ских иммунных реакций, так и формирование антиген-специфического противоопухолевого ответа [11,83]. Важную роль активации иммун-ного ответа подтверждают, в частности, экспе-рименты, проведенные в мышиной модели.…”
Section: Nepomnyashchikh Ts Et Al непомнящих тс и др Medical Imunclassified
“…The mechanisms of action of oncolytic viruses can be direct, through selective replication within neoplastic cells, or indirect through alterations of the tumor microenvironment that lead to the induction of the antitumor immune response [12,13]. Several oncolytic viruses have shown promising results for the treatment of solid and hematological tumors [14][15][16] and the possibility of using these viruses in tumor immunotherapy has emerged in recent years [17,18]. Researchers are harnessing all the characteristics of viruses, enhancing their effect on cancer cells and awakening and activating the immune system [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the DAMPs, surface‐exposed CRT and exogenous ATP serve as ‘get me’ and ‘ingest me’ indications, to the immune cells, respectively . To date, a growing number of OVs have been shown to elicit ICD in a variety of cancers . We and others recently found that oncolytic Newcastle disease virus (NDV), mediates ICD in neoplastic cells of glioblastoma, lung cancer and melanoma .…”
Section: Introductionmentioning
confidence: 99%